Relationship between body composition and the performance of physical condition in school from 6 to 16 years; systematic review (Impetus, 2021)
Instruction and objectives. In the present work a systematic review has been carried out during the last 10 years of the studies has been developed with the aim of, have carried out the studies carried out in schools from 6 to 16 years in the field of the condition physical and body composition, know its main characteristics. Material and methods. A total of 14 studies were found: 2 systematic reviews and 12 descriptive articles of the methodological process. Can identify types of analysis variables; on the one hand, those focused on physical condition and body composition, and on the other, those that introduce nutritional assessment and physical activity. Results. The analysis of the results shows that the physical condition increases with age and in turn decreases with obesity, presenting significant percentages of overweight or fat (Arnaoutis et al., 2018; Gontarev et al., 2018; Volbekiene & Griciūte, 2007). However, the prevalence in both sexes with cardiovascular risk is associated with low cardiorespiratory level and, in turn, moderate or high BMI is associated with overweight (Gulías-González et al., 2014; Cruz Estrada et al., 2017). Higher indexes are highlighted in all ages of physical condition, in children compared to strength-power and in girls flexibility-balance, highlighting that physical condition improves with age more in boys than in girls (Venckunas et al., 2018; Gulías-González et al., 2013; Bustamante et al., 2012). Finalizing it is observed according to the studies that the corporal composition has significant relation in front of the physical condition.
Keywords: body composition; physical condition; schoolchildren; Eurofit; health